Considerations and recommendations for collaborative research networks in epidemiology: Lessons learned from the diabetes LEAD Network - Tara P. McAlexander; Nora L. Lee; Gina S. Lovasi; Annemarie G. Hirsch; Melissa N. Poulsen; Brian Elbel; Lorna E. Thorpe; D. Leann Long; Leslie A. McClure (Journal of Clinical and Translational Science)
Multi-site and multi-organizational teams are increasingly common in epidemiologic research; however, there is a lack of standards or best practices for achieving success in collaborative research networks in epidemiology. We summarize our experiences and lessons learned from the Diabetes Location, Environmental Attributes, and Disparities (LEAD) Network, a collaborative agreement between the Centers for Disease Control and Prevention and research teams at Drexel University, New York University, Johns Hopkins University and Geisinger, and the University of Alabama at Birmingham. We present a roadmap for success in collaborative epidemiologic research, with recommendations focused on the following areas to maximize efficiency and success in collaborative research agreements: 1) operational and administrative considerations; 2) data access and sharing of sensitive data; 3) aligning network research aims; 4) harmonization of methods and measures; and 5) dissemination of findings. Future collaborations can be informed by our experiences and ultimately dedicate more resources to achieving scientific aims and efficiently disseminating scientific work products.